Effect of Changes in Land Use During the 20th Century on Woodland and Calcareous Grassland Vegetation in Southern Poland - Dzwonko, Zbigniew (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
In the modern agricultural landscape major threats to plant species diversity are loss and fragmentation of habitats and communities. During the last century natural and semi-natural communities have faced also cessation of tradition management and increased load of nutrients. This paper presents a survey of studies on vegetation dynamics of woodlands in the northern part of the Carpathian foothills and of calcareous grasslands on limestone hills near Kraków. The causes of fargoing changes observed in communities of these types and possible management for their conservation are discussed. The nature conservation value of woods can be assessed by means of ancient woodland plant species indicators.